PENGARUH MODAL PINJAMAN DAN MODAL SENDIRI TERHADAP TINGKAT PENDAPATAN (SHU) KOPERASI SIMPAN PINJAM FLOREDETE DESA HILIHINTIR KECAMATAN SATARMESE BARAT KABUPATEN MANGGARAI - Herman Jelatu (Pojok Publisher, 2024)
This study aims to determine the partial and simultaneous influence of loan capital and equity on the income level (SHU) of the Floredete Savings and Loan Cooperative, Hilihintir Village, West Satar Mese District, Manggarai Regency. The study uses a quantitative approach. The type of data is quantitative data collected using the documentation method, namely by collecting, recording, and reviewing data from the cooperative's financial statements. The data were analyzed using the Normality Test analysis technique, Multiple Linear Regression, t-test and f-test using the SPSS program. The results of the Normality Test show that the data is normally distributed, seen from the probability value (Asymp. Sig) of the Kolmogorov-Smirnov Test for the Loan Capital variable (0.140), Own Capital Variable (0.60) and the SHU KSP Floredete variable (0.113) greater than 0.05. Based on the Linear Regression model obtained from the analysis results, namely Y = 9.155 + 0.113X1 + (-0.203) X2, it is known that the Loan Capital variable and the Own Capital variable have an effect on the SHU of KSP Floredete, where the Loan Capital t-count is greater than the t-table (1.779>1.672) and Own Capital t-count is greater than the t-table (2.486>1.672). The results of the simultaneous test show that Loan Capital and Own Capital have a joint effect on the SHU of KSP Floredete with an f-count greater than the f-table (3.693>3.13).